Canada's Student Journal Forum: From Humble Beginnings to National Conference - Mariya Maistrovskaya; Victoria Eke; Sarah M. Forbes (Arizona State University, 2023)
Student Journal Forum began as an in-person half-day event at the University of Toronto (U of T) in 2015. It was organized by a group of librarians with the goal to connect editors of 60+ student-led U of T journals with publishing supports, best practices, and with each other. The audience's enthusiastic engagement and the community-building power of the event prompted the librarians to offer it again the next year, and the year after. Eight years later, this local annual event has grown into a Canada-wide virtual gathering. The shift to online during the COVID-19 pandemic was a key catalyst to open the Forum to students to connect remotely, and for the event to be jointly organized by multiple libraries across Canada. The event's offering has evolved as well, moving from librarian-led publishing best practice sessions to student-led presentations and participatory learning sessions. The most recent 2023 Forum featured an open call for proposals that let student editors share their experiences and present on topics that mattered to them. It was complemented by a half-day of publishing skill sessions presented by Canadian librarians and two panels with scholarly editors and publishing professionals. In this paper, we reflect on the evolution of the Student Journal Forum, its successes and challenges, and its role in establishing the connection between student editors across Canada and between different Canadian libraries that offer student journal publishing support.